2019
DOI: 10.3390/molecules24020305
|View full text |Cite
|
Sign up to set email alerts
|

Cell Responses to Extracellular α-Synuclein

Abstract: Synucleins are small naturally unfolded proteins involved in neurodegenerative diseases and cancer. The family contains three members: α-, β-, and γ-synuclein. α-Synuclein is the most thoroughly investigated because of its close association with Parkinson’s disease (PD), dementia with Lewy bodies and multiple system atrophy. Until recently, the synuclein’s research was mainly focused on their intracellular forms. However, new studies highlighted the important role of extracellular synucleins. Extracellular for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…This cooperation fosters the transmission of α-syn between cells and causes synaptic dysfunction via a signaling cascade acting through phosphorylation of Fyn kinase and activation of the N-methyl-D-aspartate receptor (NMDAR). α-syn-PrP C binding induces cofilin/actin rods formation, which changes actin dynamics, resulting in rearrangements of cytoskeleton and eventual synaptic dysfunction (Clavaguera et al, 2015; Bras et al, 2018; Surguchev et al, 2019). Equally, α-syn amyloids blocked the replication of PrP Sc in vitro and ex vivo (Aulic et al, 2017).…”
Section: The Prion-like Mechanism Of Pdmentioning
confidence: 99%
“…This cooperation fosters the transmission of α-syn between cells and causes synaptic dysfunction via a signaling cascade acting through phosphorylation of Fyn kinase and activation of the N-methyl-D-aspartate receptor (NMDAR). α-syn-PrP C binding induces cofilin/actin rods formation, which changes actin dynamics, resulting in rearrangements of cytoskeleton and eventual synaptic dysfunction (Clavaguera et al, 2015; Bras et al, 2018; Surguchev et al, 2019). Equally, α-syn amyloids blocked the replication of PrP Sc in vitro and ex vivo (Aulic et al, 2017).…”
Section: The Prion-like Mechanism Of Pdmentioning
confidence: 99%
“…In addition, Surguchev et al showed that extracellular α-synuclein interacts with cell membrane receptors such as cytoplasmic protein, lymphocyte activating gene 3, and Toll-like receptor 2. Cell signaling promotes α-synuclein to propagate between different cells [123]. The above results together indicate that in the neurons of patients with familial Parkinson's disease caused by genetic mutations, their α-synuclein pathology has sufficient seed characteristics to cause agedependent human neuronal degeneration spread in brains.…”
Section: Ipsc Models Confirm the Neuron-to-neuronmentioning
confidence: 82%
“…Several proteins such as PrPC, LAG3, neurexin1, TLR2 and mGluR5 that function as receptors for the extracellular α-synuclein have been identified [ 129 , 130 ]. The pathological effects caused due to binding of α-synuclein to cell surface receptors is under investigation and is proposed to occur by various mechanisms (for a recent review, see [ 131 ]). Ca 2+ dysregulation, synaptic dysfunction, altered glutamatergic synaptic transmission and α3-Na + /K + -ATPase activity as a result of extracellular α-synuclein have been reported [ 132 , 133 ].…”
Section: α-Synuclein: Folding Higher-order Structures and Degradamentioning
confidence: 99%